Studies of optical properties of Au nanoparticles - Zhu, Shu (2012)
It is the intent of this work to study the optical properties of Au nanoparticles. The Au nanoparticles have been synthesized with two different methods: direct-deposit self-assembly and electrodeposition. A detailed optical study of the Au nanoparticles has been performed using spectroscopic ellipsometric analysis and modeling of optical absorbance based on the Maxwell-Garnett effective medium approximation, Lorentz-Drude optical dispersion model and Beer-Lambert law. Together with the structural and material characterizations (i.e., using atomic force microscopy, scanning electron microscope and energy-dispersive X-ray spectroscopy), the study of dielectric function provides a better understanding of the fundamental physics of the Au nanoparticles (in particular, surface plasmon resonance and interband transitions) and their dependence on the intrinsic (i.e., size and shape of the nanoparticles) and extrinsic (i.e., dielectric environment around the nanoparticles, lateral near-field interaction between neighboring nanoparticles and the image charge effect of the Si substrate) effects.